2011
DOI: 10.3109/02713683.2010.551172
|View full text |Cite
|
Sign up to set email alerts
|

In VivoMonitoring of VEGF-Induced Retinal Damage in the Kimba Mouse Model of Retinal Neovascularization

Abstract: In vivo monitoring of retinal vascular and neural retinal changes in the Kimba mice using the Spectralis HRA+OCT imaging device allowed us to assess and track VEGF-induced damages in great detail and in real-time. Real-time monitoring of these changes can be used to study the interplay between VEGF overexpression and other molecular factors and to monitor dynamic retinal changes following therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Due to these constraints, interpretation of retinal histology is generally limited to the peripheralecentral axis and provides little information on the nasal-temporal and superioreinferior axes. On the other hand, the optic axis within the eye makes the retina a particularly amenable tissue for in vivo imaging studies and a number of advanced retinal imaging technologies have been used in studies of the rodent retina, including intravital confocal microscopy, angiography and optical coherence tomography (Ali Rahman et al, 2011;McLenachan et al, 2013;Paques et al, 2006Paques et al, , 2003Rakoczy et al, 2010;Ritter et al, 2005;Zhi et al, 2014). The use of techniques that are routinely used for imaging human patients in ophthalmology clinics is essential to provide a link between experimental animals and the human diseases they propose to model.…”
Section: Clinical Imaging Of Mouse Models Of Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these constraints, interpretation of retinal histology is generally limited to the peripheralecentral axis and provides little information on the nasal-temporal and superioreinferior axes. On the other hand, the optic axis within the eye makes the retina a particularly amenable tissue for in vivo imaging studies and a number of advanced retinal imaging technologies have been used in studies of the rodent retina, including intravital confocal microscopy, angiography and optical coherence tomography (Ali Rahman et al, 2011;McLenachan et al, 2013;Paques et al, 2006Paques et al, , 2003Rakoczy et al, 2010;Ritter et al, 2005;Zhi et al, 2014). The use of techniques that are routinely used for imaging human patients in ophthalmology clinics is essential to provide a link between experimental animals and the human diseases they propose to model.…”
Section: Clinical Imaging Of Mouse Models Of Diabetic Retinopathymentioning
confidence: 99%
“…A number of advanced imaging technologies have been used to study the rodent retinal vasculature, including confocal scanning laser microscopy (Mendes-Jorge et al, 2012;Paques et al, 2006;Ramos et al, 2013;Ritter et al, 2005) as well as scanning laser ophthalmoscopy and optical coherence tomography (SLO-OCT) (Ali Rahman et al, 2011;McLenachan et al, 2013;Paques et al, 2007Paques et al, , 2006Rakoczy et al, 2010;Zhi et al, 2014). Since SLO-OCT is commonly used in screening, diagnosis and staging of retinopathy in human, it is important that this technique is also used for the characterisation of mouse models of retinal vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal neovascularization is extensively observed in the Akimba and Kimba mouse models [119,122,125]. Comparable to DR patients, neovascularization in both mouse models is observed in the retina and not in the choroid [119,126].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 96%
“…The heterozygous Akita male mice develop features similar to early pathophysiological changes of diabetic complications, but fail to exhibit the advanced stage vascular dysfunctions. The non-diabetic Kimba (trVEGF029) mouse model, in which photoreceptors transiently overexpress hVEGF, is characterized by several early and advanced DR-associated vascular changes such as vascular permeability, capillary non-perfusion, microaneurysms and retinal neovascularization [119,[122][123][124][125][126][127]. It has been reported that the combination of high blood glucose levels and VEGF overexpression exacerbates the vascular complications in the Akimba mouse eye [119,127].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 99%
See 1 more Smart Citation